A Novel endo-β-1, 4-xylanase xyl-1 from Aspergillus terreus HG-52 for High-Efficiency Ramie Degumming. Issue 16 (28th November 2022) - Wu, Ya; Shu, Tong; Li, Pandeng; Wang, Zhikuan; Wang, Huihui; Pan, Fei; Li, Yingnan; Yu, Tianyi; Yu, Longjiang
ABSTRACT: Xylanase is the key enzyme responsible for the degradation of hemicellulose and plays an important role in ramie degumming. In this study, an endo-β-1, 4-xylanase xyl-1 of GH11 family from Aspergillus terreus HG-52 was cloned and identified for the first time. The protein was heterologously expressed in Escherichia coli BL21, then purified and analyzed for its biochemical properties. The optimal temperature and pH of xyl-1 are 45°C and pH 5, respectively, with a specific activity as high as 1505.11 U/mg. The immunofluorescence staining combined in-situ catalysis of ramie slices revealed that xyl-1 could degrade ramie xylan fraction. The scanning electron microscopy, X-ray diffraction, and Fourier-transform infrared spectroscopy analysis of ramie fibers treated by xyl-1 showed that the treated fibers were more dispersed, the crystallinity was improved, the absorption peak of hemicellulose functional group was reduced. Residual hemicellulose content reduced from 14.93% to 5.75% and whiteness was reached 45.4, indicating xyl-1 had high-efficiency degumming ability for ramie hemicellulose. This work excavated a promising endo-β-1, 4-xylanase for ramie fibers degumming applications and has good potential for commercial application.